2005
DOI: 10.1007/s00198-005-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in trabecular bone microstructures: global and local morphometry

Abstract: Introduction: A recently developed method allows investigating trabecular bone on an elemental (rod/plate) level. With this method, it is possible to measure local morphometric parameters such as thickness or orientation directly on the extracted rods and plates. Age-related changes of trabecular microarchitecture can thus be investigated on an elemental level, which may help to improve the understanding of age-related bone failure mechanism as well as the effect of pharmaceutical intervention in the preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 66 publications
(93 reference statements)
5
90
0
4
Order By: Relevance
“…Osteoporosis is a systemic bone disease with significant global health impacts that is characterized by low bone mass and microarchitectural deterioration, leading to increased bone fragility and fracture risk (36). Although both cortical and trabecular bone, together, determine bone strength, trabecular architecture is particularly susceptible to age-related loss because of the extensive exposure of its metabolically active surfaces and the relatively thin plates and struts (37)(38)(39)(40). Because of the documented gracilization of the human skeleton (2) and the diversity of subsistence strategies performed in the past, the hominin fossil and skeletal record is ideal for addressing questions aimed at understanding contemporary human bone biology and health.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a systemic bone disease with significant global health impacts that is characterized by low bone mass and microarchitectural deterioration, leading to increased bone fragility and fracture risk (36). Although both cortical and trabecular bone, together, determine bone strength, trabecular architecture is particularly susceptible to age-related loss because of the extensive exposure of its metabolically active surfaces and the relatively thin plates and struts (37)(38)(39)(40). Because of the documented gracilization of the human skeleton (2) and the diversity of subsistence strategies performed in the past, the hominin fossil and skeletal record is ideal for addressing questions aimed at understanding contemporary human bone biology and health.…”
Section: Discussionmentioning
confidence: 99%
“…BMD correlates strongly with bone strength and accounts for 60% to 80% of bone strength. Bone strength depends not only on the amount of mineral but also on the structural characteristics of the skeleton such as size, shape, and three-dimensional architecture [3][4][5]. Until now the prediction of bone strength and risk of fracture has mainly been based on densitometry measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that assessment of the weakest parts of the cancellous bone may lead to better prediction of fracture risk [18]. Indeed, earlier studies demonstrated that sampling bone density and microstructural parameters in smaller regions can provide better predictions of vertebral strength [19][20][21][22]. The number of samples analyzed per vertebrae, however, was usually rather limited and, depending on the techniques used (experimental, computational), dictated by minimum size requirements for meaningful analysis of a bone sample.…”
Section: Introductionmentioning
confidence: 99%